On the approximate analysis of the evolution of a plane longitudinal hyperelastic wave - Rushchitsky, J.J. (Reports of the National Academy of Sciences of Ukraine, 2019)
Three approaches (methods) are used to analyze the evolution of a plane longitudinal wave that propagates in a nonlinear hyperelastic medium — method of successive approximations, method of slowly varying amplitudes, and method of restriction on the displacement gradient. The evolution is understood as changing the initial wave profile during the propagation of a wave in the nonlinear elastic medium. Ten variants (known and new) of an approximate analysis of the evolution of a plane longitudinal wave propagating in an hyperelastic medium are described and commented. It is shown that each variant gives answer on some aspect in studying the wave evolution. An attention is drawn to the similarity and the difference in the results of analysis.